ANALYSIS OF TEACHER-PARENT INTERACTION FOR IMPROVING STUDENT ACHIEVEMENT AT MIFTAHUL ULUM ELEMENTARY SCHOOL - Abd. Rohman; Faisal Faliyandra (Universitas Islam Negeri Mataram, 2024)
This study aims to analyze the interaction strategies between teachers and parents in efforts to improve student achievement at Madrasah Ibtidaiyah Miftahul Ulum. In this research, a qualitative approach was used to deeply explore the social interactions between teachers and parents in supporting student success. Data collection techniques included interviews and observations, allowing researchers to gather direct insights from participants about their perceptions and experiences regarding this educational collaboration. The findings identified three main interaction strategies implemented by teachers: the parent-teacher association as a regular communication forum, home visits to understand students’ home environments, and a student achievement space as a medium for recognition and motivation for high-performing students. The implementation of these three strategies demonstrated a significant increase in parental involvement, contributing positively to both the academic and character development of students. This study reveals that the interactions fostered between teachers and parents can create a supportive learning environment, thereby enhancing students’ achievements holistically